Gut microbiota of provisioned and wild rhesus macaques (Macaca mulatta) living in a limestone forest in southwest Guangxi, China - Ting Chen; Yuhui Li; Jipeng Liang; Youbang Li; Zhonghao Huang (MicrobiologyOpen, 2020)
Abstract The gut microbiota plays an important role in animal health and is strongly affected by the environment. Captivity and human source food have been shown to influence drastically the gut microbiota composition and function of wild animals. Therefore, in the present study, the gut microbiota of provisioned and wild populations of limestone‐living rhesus macaques (Macaca mulatta) were compared using high‐throughput 16S rRNA sequencing and bioinformatic analyses. The results indicated that provisioned macaques had a higher microbial richness than wild macaques, but there was no significant difference in the evenness of the gut microbiota between the two populations. Provisioned macaques also showed a higher abundance of Firmicutes and a lower abundance of Bacteroidetes than wild macaques. Functional analysis revealed that wild macaques had enriched microbial pathways involved in glycan biosynthesis and metabolism, transport and catabolism, and the digestive and endocrine systems, while provisioned macaques were richer in pathways associated with signaling molecules and interaction, neurodegenerative diseases. These differences were likely due to modification of the gut microbiota of the provisioned macaques to enable the digestion of new foods.